UPAYA ORANG TUA DALAM PENDIDIKAN ANAK USIA DINI MENURUT PENDIDIKAN ISLAM - Iwan Setiawan (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2013)
The research objective is the efforts of parents in educating early childhood education in Islam. Method in this study is a qualitative method that results in early childhood education in Islam Islamic view of the role of educational attainment that the Islamic religion in particular to foster awareness in children from an early age through various examples of habituation, a story, a good example of the elderly and teachers were then given an explanation and understanding in accordance with the level of thinking about the norms and values of society and religion, including the efforts of parents; educate children with Hiwar (dialogue), educating children with the story, the parable, by example, by training and practice, with 'ibrah and mauizhah, with targhib and Tarheeb.